2008
DOI: 10.1002/hep.22493
|View full text |Cite
|
Sign up to set email alerts
|

A 20-year single-center experience with acute liver failure during pregnancy: Is the prognosis really worse?

Abstract: Pregnant patients with acute liver failure (ALF) are believed to have a worse outcome than nonpregnant women and men with ALF. However objective data supporting this supposition are scant. Therefore, the current study compared the outcome, complications, and causes of ALF among pregnant women and girls with age-matched nonpregnant women and girls and men and boys with ALF. One thousand fifteen consecutive ALF patients in the reproductive age group, admitted at the All India Institute of Medical Sciences, New D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
142
1
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(153 citation statements)
references
References 33 publications
5
142
1
5
Order By: Relevance
“…In ALF, rapid immune paralysis is well known and overt sepsis has been reported in 55%-90% of patients. 19 A strong association between occurrence of infection and course of encephalopathy has been clearly documented. 3,20 In a prospective evaluation of 96 acetaminophen induced ALF cases with early encephalopathy, occurrence of infection was associated with progression of encephalopathy to deeper grades in about 80% of the individuals.…”
Section: Infections and Systemic Inflammatory Response Syndrome (Sirsmentioning
confidence: 98%
“…In ALF, rapid immune paralysis is well known and overt sepsis has been reported in 55%-90% of patients. 19 A strong association between occurrence of infection and course of encephalopathy has been clearly documented. 3,20 In a prospective evaluation of 96 acetaminophen induced ALF cases with early encephalopathy, occurrence of infection was associated with progression of encephalopathy to deeper grades in about 80% of the individuals.…”
Section: Infections and Systemic Inflammatory Response Syndrome (Sirsmentioning
confidence: 98%
“…Indian epidemics of hepatitis E virus have shown that pregnant women especially in their second and third trimesters get infected more frequently (12-20%) than men and non-pregnant women (2-4%) for unclear reasons. 18 Even the mortality rate is significantly higher among pregnant women who develop hepatitis during epidemics (10-39%) than in the general population affected with hepatitis (0.06-12%). In the sporadic setting, evidence of HEV infection has been detected in 30-45% of patients with ALF.…”
Section: Acute and Subacute Liver Failurementioning
confidence: 99%
“…One study found that progesterone receptor gene mutations (PROGINS) occur more frequently among pregnant female patients with ALF and these patients also had high viral load leading to poor pregnancy outcomes in hepatitis E. 19 Once the pregnant females develop ALF, mortality is similar to that of non-pregnant women and men with ALF, and is independent of the cause or trimester. 18 Acute Fatty Liver of Pregnancy is related to genetic predisposition, and may also have geographical variation in prevalence.…”
Section: Acute and Subacute Liver Failurementioning
confidence: 99%
See 2 more Smart Citations